The Evolution of Zoonosis-Related Studies in Indonesia, 1977-2023: Bibliometric Analysis Concepts - Nurjanah, Diana; Dharmayanti, Indi; Fadilah, Fadilah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
Various zoonotic diseases have been reported as epidemics throughout the world, including in Indonesia. Various studies have been conducted related to gaps in knowledge, especially on disease distribution, etiology, pathogens, hosts, vector biology, dynamics, cycle of transmission, predisposing factors, and risk factors. To find out the dynamics of zoonotic disease study and research in Indonesia, a study was conducted to report a literature analysis that focused on bibliometric analysis of the Scopus database and VOSviewer software to create a visualization map that identified how the evolution of zoonotic diseases studies from 1977-2023 in Indonesia. In co-occurrence analysis, two units of analysis are used, namely "author keywords" and "index keywords" in VOSviewer. It showed that studies related to zoonoses in Indonesia tend to increase every year with a significant increase in 2020 and 2022. Document types are dominated by articles (72%) with subjects or research areas related to â€œmedicineâ€ (29%). From the "author keywords" analysis unit, the words "zoonosis" and "Indonesia" were the words that appeared the most. Meanwhile, from â€œindex keywordsâ€ six clusters were found with the word "human" "animals", and "zoonosis" being the word that appears the most in the analysis of the studies conducted.